Lectotypification and correct name for Neoscirpus dioicus (Cyperaceae) - Son, Dong Chan; Chang, Kae Sun; Kim, Yoon-Young; Park, Yu Chul; Kim, Hyun-Jun; Oh, Seung-Hwan (Phytotaxa, 2019)
As part of an ongoing project promoted by the Korea National Arboretum, aimed at tracing the original materials used to describe vascular plant taxa in Korea, we detected problems with the typification of Neoscirpus dioicus Y.N.Lee & Y.C.Oh (2006b: 25) and some nomenclatural issues related to that name.